Eradication of Typhus Exanthematicus in Bosnia and Herzegovina - Zlatko Puvačić; Edina Bešlagić; Šukrija Zvizdić; Sandra Puvačić; Jelena Ravlija; Sadeta Hamzić (Biomolecules & Biomedicine, 2006)
Typhus exanthematicus in Bosnia and Herzegovina held in endemic areas from which especially quickly began spread after 1945. That year, in 1945, one hundred epidemics of typhus fever appeared, with the highest incidence rate in Europe of 215.04 per 1,000. Directions of unique program in the world were to eradicate lice of the body, but also establish monitoring of the recidivism, Brill-Zinsser disease. Since 1971, typhus exanthematicus (classical typhus) hasn't appeared in Bosnia and Herzegovina, so epidemic typhus can considered as an eradicated communicable disease.